Molecular Detection of Colistin-Resistant E. coli in Village Chickens from Kelantan, Malaysia - Habiba Lawal; Shamsaldeen Ibrahim Saeed; Nor Fadhilah Kamaruzzaman; Zarizal Suhaili; Gaddafi Mohammed Sani; Mulu Lemlem; Qiya Yang; Erkihun Aklilu (Bacteria)
Pathogenic Escherichia coli can cause a variety of intestinal and extra-intestinal infections in humans and animals. The availability and subsequent misuse of antimicrobials, especially in poultry production systems, has contributed immensely to the emergence and spread of multidrug-resistant E. coli. This study investigated the genotypic characterization of colistin-resistant E. coli and selected antimicrobial-resistance encoding genes along with their phenotypic resistant pattern and the multiple antimicrobial resistant (MAR) index from village chickens in Kelantan. Sixty E. coli isolates obtained from a previous study’s stock culture were enriched and analyzed using routine microbiological methods: Kirby–Bauer disc diffusion method, minimum inhibitory concentration (MIC), and PCR amplification of E. coli species-specific and multidrug-resistance mcr-positive E. coli. All the isolates were confirmed as E. coli and 16.6% (10/60) were positive for mcr. Five isolates were positive for mcr-1, three for mcr-4, and two for mcr-9. The mcr-positive isolates showed varying degrees of resistance to different antimicrobials. The isolates were resistant to gentamicin (100%), chloramphenicol (100%), and tetracycline (89.4%) and susceptible to ceftaxidime (2.26%) and imipenem (18%). Furthermore, 100%, 94.7%, and 89.4% of isolates from village chickens belonged to phylogroup C, B2, and E, while 21.0% and 42.1% of the isolates belonged to phylogroup A and B1, respectively. Sequence types (STs) of selected E. coli isolates were further analyzed using multi-locus sequence typing, and 10 different STs were identified. This study showed the emerging threats of multidrug-resistant mcr-positive E. coli gene in village chickens that are believed to be raised with minimal or no antibiotics.